PENGGUNAAN KINESIOTAPE SELAMA TIGA HARI TIDAK BERBEDA DENGAN PEREKAT PLASEBO DALAM MENGURANGI RESIKO CEDERA BERULANG DAN DERAJAT Q-ANGLE PADA PENDERITA PATELLOFEMORAL PAIN SYNDROME - -, Abdurrasyid; Sutjana, Dewa Putu; Irfan, Muhammad (Sport and Fitness Journal; Volume 2, No.1, 2014)
Many athletes who suffer Patellofemoral Pain Syndrome (PFPS), they using kinesiotape while playing or less than two weeks, this condition make a question of there are efficacy when used kinesiotape while playing and practicing. The purpose of this study to ensure the use of kinesiotape for three days did not differ with adhesive placebo in reducing the risk of repetitive injury and q-angle in patients with patellofemoral pain syndrome (PFPS). The experimental research method to design randomized clinical trial design. Sample of 17 athletes who suffer from PFPS and time of observation for three days. Divided into two groups, kinesiotape groups (n = 9) as the treatment and placebo groups (n = 8) as a control. Measurement instruments used were Functional Movement Screening (FMS) and Q-angle. The results of this study, kinesiotape group able to reduce the risk of repetitive injury with p = 0.002 (p <0,05). Placebo group was also able to reduce the risk of repetitive injury p = 0.01 (p <0,05). Kinesiotape able to decrease q- angle with p = 0.004 (p <0,05). Placebo group was also able to reduce the q-angle with p = 0.008 (p <0,05). At different test measurements FMS using independent t-test p = 0.777 (p> 0.05), and a different test with q-angle measurements using the Mann-Whitney test p = 0.63 (p> 0,05). The conclusion that the use of kinesiotape and adhesives placebo can reduce the risk of recurrent injury and the degree of q-angle for three days. It is clear that using kinesiotape have the same effectiveness with placebo were not elastic adhesive while playing a game and practicing.
Keywords: kinesiotape, repeated injury, q-angle, patellofemoral pain syndrome, functional movement screening.